Scaling, unwinding and greening QE in a calibrated portfolio balance model - Jesper Riedler; Tina Koziol (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We develop a portfolio balance model to analyze the impact of euro area quantitative easing (QE) on asset yields. Our model features two countries each populated by two agents representing their respective banking and mututal fund sectors. Agents, which differ in their preferences for assets, can trade currencies, bonds and equities. In simulations of the calibrated model we find that 10-year euro area bond returns decline by 31 basis points in response to exteuro1 trillion in central bank bond purchases, which is in line with the empirical literature. QE leads to a substantial flattening of the yield curve and increasing the maturity of purchased bonds increases the average yield impact. When QE is unwound, yields increase quicker than the central bank balance sheet shrinks. This is because the yield impact scales non-linearly with increasing asset purchases. When assessing the potential impact of green QE, we find that it is slightly less effective in reducing bond yields than conventional QE. However, the spread between green and brown bond yields decreases with conventional QE while it increases with green QE.
Keywords: C63; G11; E52; 330; euro area QE; portfolio balancing channel; yield curve; green QE